Environmental, social, and governance practices and reporting readiness in small and medium-sized enterprises - Kozłowska, Justyna; Ustinovičius, Leonas (Technological and Economic Development of Economy, 2025)
Following the European Sustainability Reporting Standards (ESRS), in 2026, the non-financial reporting obligation will be extended to small and medium-sized enterprises listed on the regulated market and meet employment and financial criteria. The obligation will also affect their contractors, suppliers, customers, and all stakeholders that influence a company’s overall Environmental, Social, and Governance (ESG) performance. The study aims to identify the Small and Medium-sized Enterprises’ (SME) practices in the field of ESG and recognise whether they are ready to report on their ESG activities. A quantitative method was used to obtain a general picture of the approach to ESG practices. The study was conducted among 300 Polish companies. The study results show that about half of the surveyed small and medium-sized enterprises conduct ESG activities and monitor ESG indicators. More than half demonstrate basic or good readiness for ESG reporting following the adopted criterion. This study’s contribution is twofold. First, it enriches the current state of knowledge by adding original insights into the ESG practices of SMEs, while most existing studies focus on the ESG activities of large enterprises. Second, the study’s novelty is its attempt to assess the readiness for ESG reporting at the corporate and country levels.